Two new predatory nematode species Iotonchus helicus sp.nov. and Iotonchus thui sp.nov. (Nematoda: Mononchida) from Vietnam - Thanh, Nguyen Vu (Academia Journal of Biology, 2014)
The free-living soil nematode and aquatic nematode fauna of Vietnam has been investigated recently. During the last 10 years, approximately 300 free-living nematode species were identified for the Vietnamese fauna; among them, more than 40 species have been described as new to science. Below, the description of two new predatory nematode species to science Iotonchus helicus sp.nov. and Iotonchus thui sp.nov. (Nematoda: Mononchida) are given. Iotonchus helicus Nguyen Vu Thanh sp.nov. Female: body ventrally arcuate to C-shaped when relaxed. Lip region distinctly not set up contour of body by the neck expansion and 34.2-41.4 mm wide; its high equalled 9-11.7 mm. Amphid pore is small, 2.9-5.4 wide and located at 12.6-20.7 mm from anterior end of body and 28-39 mm from base of the buccal cavity. Buccal cavity nearly 2 as long as wide, 36-45 mm long, 19.8-27.9 wide. Dorsal tooth small and basal, its apex located at 15-21.4% from base. Oesophagus muscular, its intestinal junction weakly tuberculated. Excretory pore not observed. Genital system didelphic amphidelphic. Vulva post-equatorial, transverse, lips sclerotized, off-set from the body cuticle. Vagina cylindroid, less than one half body width deep. Uterus short, sphincter not observed at the oviduct-uterus junction. Tail conoid, arcuate, gradually tapering with slightly bulging tip, 178-260 mm long or 4.3-6 anal body width long. Caudal glands and terminal spinneret subterminal. Remarks: the new species Iotonchus helicus sp.nov. closely resembles I. rayongensis Buangsuwon & Jensen, 1966; I. thailandensis Buangsuwon & Jensen, 1966 and I. basidontus Clark, 1960. From I. Rayongensis, it differs in having a shorter body length, shorter tail length, ratio “a” and ratio “c” (in I. rayongensis L = 1.97 mm; L tail = 350 mm; a = 37; c = 9.5). Further, it can be differentiated from I. thailandensis in having an anterior position of vulva, ratio “a” and shaped tail (a = 38-48; V = 56-66%; and the tail with pointed tip in I. thailandensis). From I. Basidontus, it differs in having a shorter body length, shorter tail length, smaller stoma and ratio “a” (L = 1.8-2.4 mm; L tail = 270-360 mm; stoma = 50-55 mm long and 25-32 mm wide; a = 30-32 mm in I. basidontus). Iotonchus thui Nguyen Vu Thanh sp.nov. Female: nematode of medium size, 2.8 mm body length. Body after fixation ventrally curved to C-shaped generally more curved in posterior half. Cuticle abaut 5,4 mm thick in the middle of the body and up to 8.4 mm on the dorsal side of the tail. Lip region distinctly set up contour of body by the neck expansion. Amphid 5-6 mm width, cup-shaped, located at 17-22 mm from anterior end of body. Dorsal tooth very shape, situated in posterior one-thisd, directed forward. Dorsal tooth apex located at 76-81% of the buccal cavity length. Excretory pore well developed. Rectum 39-45 mm or less than one anal body width long. Genital system didelphic, amphidelphic. Sphincter well developed at the junction of the oviduct and ovaries. Uterus relatively short, vagina cylindrical. Vulva a transverse slit. Advulval papillae absent. Tail conical ventrally curved, 105-165 mm or 2.4-3.5 anal body diameter with finely rounded tip. Two caudal pores, three caudal papillae on each side. Caudal reduced, spinneret absent. Male: general appearance similar to female. Amphid larger than that of female. Number of supplements 18-24. Spicules moderately slender, ventrally curved, and 1.7 time as long as anal body width. Gubernaculum well developed. Lateral guiding pieces thickening torwards the extremity which is forked. Tail similar to female but somewhat shorter. Two caudal pores, three pairs of subventral papillae and one pair of subdorsal papillae. Caaudal glands more reduced than female, spinneret absent. Remarks: the new nematode species Iotonchus thui sp.nov. closely resembles I. acutus Cobb, 1917, but differs from it in having a longer body, longer tail and more supplements in males (in I. acutus, L = 1.6-2.4 mm; L tail = 120-170 mm; supplement = 9-12).